2022
DOI: 10.1038/s41538-022-00128-4
|View full text |Cite
|
Sign up to set email alerts
|

Snow flea antifreeze peptide for cryopreservation of lactic acid bacteria

Abstract: Cryogenic machining is one of the most commonly used techniques for processing and preserving in food industry, and traditional antifreeze agents cannot regulate the mechanical stress damage caused by ice crystals formed during recrystallization or thawing. In this study, we successfully developed an express system of a novel recombinant snow flea antifreeze peptide (rsfAFP), which has significant ice recrystallization inhibition ability, thermal hysteresis activity and alters ice nucleation, thus regulating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…4 Numerous studies have shown that cell membrane damage caused by ice crystals and cold-induced denaturation or inactivation of intracellular sensitive enzymes can lead to decreased cellular metabolic activity during freezing stress. 3,6 The metabolic activity of bacterial cells added with diverse antifreeze agents after freezing stress was analyzed by reducing the artificial electron acceptor INT to the visible intracellular deposits of INT-formazan, which was related to cellular dehydrogenase and reductase activity of living bacteria. 21 The results in Figure 2B showed that the residual metabolic activity of bacterial cells in the control group was (23.87 ± 3.46)%.…”
Section: Identification and Verification Of Antifreezementioning
confidence: 99%
See 1 more Smart Citation
“…4 Numerous studies have shown that cell membrane damage caused by ice crystals and cold-induced denaturation or inactivation of intracellular sensitive enzymes can lead to decreased cellular metabolic activity during freezing stress. 3,6 The metabolic activity of bacterial cells added with diverse antifreeze agents after freezing stress was analyzed by reducing the artificial electron acceptor INT to the visible intracellular deposits of INT-formazan, which was related to cellular dehydrogenase and reductase activity of living bacteria. 21 The results in Figure 2B showed that the residual metabolic activity of bacterial cells in the control group was (23.87 ± 3.46)%.…”
Section: Identification and Verification Of Antifreezementioning
confidence: 99%
“…Due to its low production cost and stable properties, foodborne hydrolyzed antifreeze peptides are widely used in the food and biomedical fields. There has been growing interest in obtaining antifreeze peptides from natural food sources in recent years. Takifugu obscurus skin is rich in collagen, which is a good source to produce antifreeze peptides and is usually just discarded as food processing waste. Thus, the utilization of the aquatic byproducts presents an opportunity for application in the biomedical and food industries.…”
Section: Introductionmentioning
confidence: 99%
“…The devices for vitrification are various, such as cyrotop (for oocytes) ( Miao et al, 2022 ), plastic straw (for spermatids) ( Patra et al, 2021 ), and cryomesh (for islets) ( Zhan, Rao, et al, 2022 ). However, low temperature can cause a range of damage to biological samples, including protein denaturation ( Chen et al, 2022 ), membrane damage ( Lee et al, 2023 ), oxidative stress ( Gualtieri et al, 2021 ). Since DMSO was first used in bull sperm cryopreservation in 1959, it has been found that the addition of a certain concentration of DMSO could resist these cryodamages ( Lovelock and Bishop, 1959 ; Stubbs et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%